Melatonin protects against paraquat‐induced damage during in vitro maturation of bovine oocytes - Pang, Yun‐Wei; Jiang, Xiao‐Long; Wang, Ya‐Chun; Wang, Yang‐Yang; Hao, Hai‐Sheng; Zhao, Shan‐Jiang; Du, Wei‐Hua; Zhao, Xue‐Ming; Wang, Lin; Zhu, Hua‐Bin (Journal of pineal research, 2019)
Paraquat (PQ), a broad‐spectrum agricultural pesticide, causes cellular toxicity by increasing oxidative stress levels in various biological systems, including the reproductive system. PQ exposure causes embryotoxicity and reduces the developmental abilities of embryos. However, there is little information regarding the toxic effects of PQ on oocyte maturation. In this study, we studied the toxic effects of PQ exposure and the effects of melatonin on PQ‐induced damage in bovine oocytes. PQ exposure disrupted nuclear and cytoplasmic maturation, which was manifested as decreased cumulus cell expansion, reduced first polar body extrusion, and abnormal distribution patterns of cortical granules and mitochondria. In addition, PQ treatment severely disrupted the ability of the resulted in vitro‐produced embryos to develop to the blastocyst stage. Moreover, PQ exposure significantly increased the intracellular reactive oxygen species (ROS) level and early apoptotic rate, and decreased the glutathione (GSH) level, antioxidative CAT and GPx4 mRNA, and apoptotic‐related Bcl-2/Bax mRNA ratio. These results indicated that PQ causes reproductive toxicity in bovine oocytes. Melatonin application resulted in significant protection against the toxic effects of PQ in PQ‐exposed oocytes. The mechanisms underlying the role of melatonin included the inhibition of PQ‐induced p38 mitogen‐activated protein kinase (MAPK) activation, and restoration of abnormal trimethyl‐histone H3 lysine 4 (H3K4me3) and trimethyl‐histone H3 lysine 9 (H3K9me3) levels. These results reveal that melatonin serves as a powerful agent against experimental PQ‐induced toxicity during bovine oocyte maturation and could form a basis for further studies to develop therapeutic strategies against PQ poisoning.